Grenada : the jewel despoiled - Lewis, Gordon K (John Hopkins University BaltimoreUS, 1987)
Presents account of Grenadian politics and American interventionism considering their implications for all West Indian nations. Places the Grenada revolution in the context of Caribbean history and gives brief history of the island. Describes the decadent Gairy regime and the rise of the socialist New Jewel Movement. Discusses the coup d'etat and achievement of the revolution. Analyses stresses and strains of the PRG Cabinet, party and Central Committee. Retells events that led to execution of Maurice Bishop. Outlines roles of the ultra left Coard faction, the Caribbean Bourgeoisie, and US imperialism in overthrowing the revolution. Points out lessons for the Caribbean State System and the Caribbean left.